Aktualisasi Kepribadian Demokratis di Perguruan Tinggi Keagamaan Islam Negeri Aceh - Chairan M Nur; Harri Santoso (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
The world of education is expected to be able to be democratic. Universities as a collection of academic actors who have broad insight and are aware of their different rights must of course be the pioneers of actualizing democratic personality and it is hoped that there will be no discrimination even if only a little. The purpose of this study was to determine the personality of educators at Aceh State Islamic Religious Colleges; and the attitude of students towards the personality of educators at the Aceh State Islamic Religious College. This research is field research, with the type of qualitative research. The subjects of this study were Lecturers and Students at the State Islamic Religious College (PTKIN) Aceh consisting of IAIN Lhokseumawe Campus, STAIN Meulaboh, and UIN Ar-Raniry Banda Aceh. Data collection techniques using closed interviews and questionnaires. The results showed that the Personality Actualization of Educators at Aceh State Islamic Religious Colleges had been actualized well. This is based on the results of interviews with lecturers at three Aceh State Islamic Religious Universities. and Students' Attitudes towards the Personality of Educators at Aceh State Islamic Religious Colleges based on the results of the questionnaire analysis.